The efficacy and duration of treatment with propranolol in children with cyclic vomiting syndrome in southern Iran - Mahmoud Haghighat; Hajar Memari; Naser Honar; Seyed Mohsen Dehghani; Mohammad-Hadi Imanieh; Seyed-Javad Injoo; Hazhir Javaherizadeh (Gastroenterology Review)
Introduction : Cyclic vomiting syndrome is a functional disorder characterised by repeated episodes of nausea and vomiting with symptom-free intervals between the attacks. Cyclic vomiting syndrome is a migraine equivalent; therefore, anti-migraine medications are effective for cyclic vomiting syndrome prophylaxis, but duration of treatment is not clear. Aim : To determine the efficacy and duration of drug therapy in cyclic vomiting syndrome. Material and methods : This study was conducted on 206 cases of cyclic vomiting syndrome, who were treated with propranolol as prophylaxis. After they were symptom-free for at least 9 months, propranolol was tapered and discontinued and then they were followed for at least 6 months after drug withdrawal for evaluation of recurrence. Results : The study subjects included 127 boys and 79 girls. The mean age of symptom onset was 3.4 years (range: 3 months to 14.5 years) and the mean age at the time of diagnosis was 5.7 years (range: 8.4 months to 18 years). Among the 206 patients in whom propranolol was discontinued, only 16 (7.8%) subjects developed recurrence of symptoms in the 6-month follow-up period. Conclusions : There is no need to continue prophylaxis of cyclic vomiting syndrome for a long time. It is also possible to make the duration of drug therapy shorter, which is useful for the convenience of the patients and prevention of drug side effects.